“Mother-researcher”: articulations and practicalities in a research on care (Anuário Antropológico, 2023)
This article proposes to reflect on practices of doing research on care, from the place of a “mother-researcher”, based on an ethnographic experience in a rural Commune located in a settlement in the rural area of Rio Grande do Sul (BR). Inspired by María Puig de la Bellacasa, we consider that ethics of doing research does not live in a “subjective” and difficult-to-access place, but it’s located in daily care practices, crossed by the possibilities of being “touched”, both in the material as well as affective sense. From scenes experienced in the fieldwork, in which being a researcher and a mother provoke a privileged situation, the concepts of “kin” and “touching visions” are rescued in order to perceive the boundaries between “me” and “other” as blurred, enabling relationships, creating reciprocal connections and articulations between being, whether human or not